Images of Place, Secularity and Gentrification: On Urban Religious Belonging in an Inner City Neighbourhood in Oslo - Thorstensen, Erik (Secularism and Nonreligion, 2021)
Through extensive fieldwork conducted in an inner city neighbourhood in Oslo, Norway, the authors found that a variation of actors and settings evoked different religious and secular images of place. In what ways is the urban experience shaping or challenging the religious sense of spatial belonging, and why is a secular discourse dominating the scene? In order to obtain such images and sense of place in the context of a recently established area based initiative, we interviewed representatives for the religious communities localized in the neighbourhoods of Tøyen and Grønland. Here we encountered no religiously infused language despite a sizeable spatial religious presence. In the sciences of religion, the view of a separation between the secular and the religious as a social fact and a social norm in modern societies dominates. We argue that there is a privatization of religion (Casanova 1994) within the larger discourse of urban renewal and gentrification. Simultaneously we find the reverse of Taylor's (2007) proposal of the emptying of religion in social space: namely a filling up of religion in social spaces, that we label "urban religious belonging". This article provides further empirically based knowledge into the connection of religion, secularism and the urban sphere, the difference between belief and representations or discourses, as well as a methodological approach for studying these connections and fractures.